Clinical Supervision Model to Improve the Quality of Learning in Elementary School - Rosleny Babo; Agustan Syamsuddin (Jurnal Ilmiah Sekolah Dasar, 2022)
The implementation of the supervision of the principal so far has not been running as it should, even though this is an essential thing to increase teacher competence. This study aims to improve the quality of learning by implementing clinical supervision of the learning process carried out by elementary school teachers. This type of research is a school action research that aims to improve the situation or make school innovations to improve the quality of learning to produce students who think critically, creatively, innovatively, proficiently in solving problems. The design of this clinical supervision model consists of several stages, namely the meeting stage, the observation stage, and the feedback meeting stage. The subjects in this study were 12 school teachers. It collects data using observation techniques using observation sheets developed based on the clinical supervision model. From the results of the clinical supervision observation data analysis, it can be seen that the learning scores in the first cycle have increased in the second cycle. The average score in the first cycle is 70.00. Meanwhile, the average score in the second cycle increased by 95.00. The process of implementing the application of clinical supervision research instruments, observing the learning process, and conducting learning assessments. The analysis of the meeting stage was carried out to identify the strengths and weaknesses of the teacher in the learning process. Based on the results and research findings, it can be said that clinical supervision carried out in schools can improve the quality of teacher learning in terms of developing learning tools, implementing learning, and learning reflection.